Определитель видов рода Stictopleurus Stаl, 1872 (Heteroptera, Rhopalidae) фауны Советского Союза - Пучков, В.Г. (Вестник зоологии, 1978)
The key of ten species from the Stictopleurus Stal genus and information of their distribution are presented. S. murinus Putshkov, sp. n. is described.